Coalesce

# Coalesce - x →∞ ln x x − 1 = ” ∞ ∞ ” = lim x...

This preview shows pages 1–2. Sign up to view the full content.

In the trig section we needed lim h 0 sin h h =” 0 0 ”=1 lim h 0 cos h 1 h =” 0 0 ”=1 We used a geometrical argument to solve it, but there are a lot of those functions with an indeterminant form 0 0 ”or” ” like lim x 1 ln x x 1 =” 0 0 lim x →∞ ln x x 1 =” here we can use L’Hospitals Rule : If f,g are diF. and g 0 ( x ) 6 = 0 near a (except possibly at a) and if lim x a f ( x ) = 0 and lim x a g ( x ) = 0 (i.e. we have ” 0 0 ”) or lim x a f ( x )= ±∞ and lim x a g ( x )= ±∞ (i.e. we have ” ”) then lim x a f ( x ) g ( x ) = lim x a f 0 ( x ) g 0 ( x ) I± the limit on the right side exists (or is ±∞ ) Remarks: L’Hospital says that the limit of the quotient a two functions is equal to the limit of the quotient of their derivatives , provided the given conditions It can also be used for one sided limits or if a = ±∞ – Proof for the case f ( a )=0= g ( a ): lim x a f 0 ( x ) g 0 ( x ) = f 0 ( a ) g 0 ( a ) = lim x a f ( x ) f ( a ) x a lim x a g ( x ) g ( a ) x a = lim x a f ( x ) f ( a ) g ( x ) g ( a ) = lim x a f ( x ) g ( x ) So now we can solve lim h 0 sin h h =” 0 0 ” = lim h 0 cos h 1 =1 lim h 0 cos h 1 h =” 0 0 ” = lim h 0 sin h 1 =0 lim x 1 ln x x 1 =” 0 0 ” = lim x 1 1 /x 1 =1 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
lim
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x →∞ ln x x − 1 = ” ∞ ∞ ” = lim x →∞ 1 /x 1 = 0 lim x →∞ x − 1 x 2 = ” ∞ ∞ ” = lim x →∞ 1 2 x = 0 lim x →∞ x 2 − 1 2 x 2 + 1 = ” ∞ ∞ ” = lim x →∞ 2 x 4 x = 1 / 2 lim x →∞ e x x 2 = ” ∞ ∞ ” = lim x →∞ e x 2 x = ” ∞ ∞ ” = lim x →∞ e x 2 = ∞ lim θ → tan θ − θ θ 3 = ” ” = lim θ → sec 2 θ − 1 3 θ 2 = = lim θ → 2 sec 2 θ tan θ 6 θ = lim θ → sec 2 θ tan 2 θ + 2 sec 4 θ 6 = 1 / 3 lim x → + x ln x = lim x → + ln x 1 /x = ” −∞ ∞ ” = lim x → + 1 /x − 1 /x 2 = lim x → + x = 0 • But be careful! Since 1 − cos π = 2 6 = 0 this is wrong : lim x → π − sin x 1 − cos x 6 = lim x → π − cos x sin x = −∞ 2...
View Full Document

{[ snackBarMessage ]}

### Page1 / 2

Coalesce - x →∞ ln x x − 1 = ” ∞ ∞ ” = lim x...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online